(untitled) (Ustozlar uchun, 2025)
This article examines language as a phenomenon that combines communication and thinking. Language allows people to exchange information, express emotions, and interact in society while also shaping human thought. The article considers linguistic and cognitive approaches, including linguistic relativity and cognitive linguistics. Language is viewed not only as a system of signs but as a key mechanism for understanding and interpreting reality.